The Relationship between Child Maltreatment and Emotion Recognition - Koizumi, Michiko (Public Library of Science, 2014)
Child abuse and neglect affect the development of social cognition in children and inhibit social adjustment. The purpose of this study was to compare the ability to identify the emotional states of others between abused and non-abused children. The participants, 129 children (44 abused and 85 non-abused children), completed a children’s version of the Reading the Mind in the Eyes Test (RMET). Results showed that the mean accuracy rate on the RMET for abused children was significantly lower than the rate of the non-abused children. In addition, the accuracy rates for positive emotion items (e.g., hoping, interested, happy) were significantly lower for the abused children, but negative emotion and neutral items were not different across the groups. This study found a negative relationship between child abuse and the ability to understand others’ emotions, especially positive emotions.